2019
DOI: 10.3390/molecules24030497
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Arylamidine Derivatives as Serotonin/Norepinephrine Dual Reuptake Inhibitors

Abstract: To improve the in vivo antidepressant activity of previously reported serotonin (5-HT) and norepinephrine (NE) dual reuptake inhibitors, three series of arylamidine derivatives were designed and synthesized. The in vitro 5-HT and NE reuptake inhibitory activities of these compounds were evaluated, and compound II-5 was identified as the most potent 5-HT (IC50 = 620 nM) and NE (IC50 = 10 nM) dual reuptake inhibitor. Compound II-5 exhibited potent antidepressant activity in the rat tail suspension test and showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Based on the previous studies [ 167 ] and in a quest to discover potential lead(s) for antidepressant-like activity, Wen et al . designed and synthesized a series of arylamidine derivatives (Fig.…”
Section: Various Classes Of Multi-target Directed Ligands Against Dep...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous studies [ 167 ] and in a quest to discover potential lead(s) for antidepressant-like activity, Wen et al . designed and synthesized a series of arylamidine derivatives (Fig.…”
Section: Various Classes Of Multi-target Directed Ligands Against Dep...mentioning
confidence: 99%
“…Acute toxicity studies were performed at the dose of 200 and 400 mg/kg after 20h and results demonstrated that compound 72a exhibited low toxicity with LD 50 value >400 mg/kg. SAR studies suggested that the substitution with electron-withdrawing groups at the phenyl ring increased the binding affinities, whereas that of electron-donating groups decreased the affinities [ 167 ].…”
Section: Various Classes Of Multi-target Directed Ligands Against Dep...mentioning
confidence: 99%
“…Wen et al. designed and synthesized three series of piperazine bearing arylamidine derivatives to improve antidepressant activity earlier reported 5‐HT receptors ligands [103] . Initially, synthesized compounds were screened for in vitro serotonin (5‐HT) and norepinephrine (NE) reuptake inhibitory activity.…”
Section: Recent Advancements In Piperazine Derivatives As Antidepressantsmentioning
confidence: 99%